Differences in Severity and Emotions for Public and Private Face-to-Face and Cyber Victimization Across Six Countries. (September 2017) - Wright, Michelle F.; Yanagida, Takuya; Aoyama, Ikuko; Ševčíková, Anna; Macháčková, Hana; Dědková, Lenka; Li, Zheng; Kamble, Shanmukh V.; Bayraktar, Fatih; Soudi, Shruti; Lei, Li; Shu, Chang
The purpose of this study was to examine the role of medium (face-to-face, cyber) and publicity (public, private) in perceptions of severity and emotional responses to victimization among adolescents from China, Cyprus, the Czech Republic, India, Japan, and the United States, while controlling for gender, individualism, and collectivism. There were 3, 432 adolescents (age range = 11-15 years, 49% girls) included in this study. They read four hypothetical victimization scenarios, which were manipulated based on the medium and publicity, including public face-to-face victimization, private face-to-face victimization, public cyber victimization, and private cyber victimization. After reading the scenarios, adolescents rated the severity of each scenario and their feelings of anger, sadness, and embarrassment following victimization. Overall, higher severity related to each of the emotional responses. Furthermore, greater perceptions of severity increased adolescents' feelings of anger, sadness, and embarrassment more often for public victimization and face-to-face victimization than for private victimization and cyber victimization. Some variations were found in these associations based on country of origin. The findings from this study indicate that perceived severity and emotional responses are different in various victimization contexts. Therefore, it is important to consider various victimization contexts.